Pengaruh Murottal Al-Qur’an Terhadap Tingkat Konsentrasi Anak Kelas V Dengan Gangguan Konsentrasi Belajar Di Desa Sriamur Tahun 2020 - Mohammad Ali; Ganesa P.D Kurniawan; Amelia Rezeki Andriani (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Introduction: Concentration is an important aspect because it is related to the effort to focus attention on an object so that it can understand and understand the object that is considered in detail and is very much needed in the learning process. To increase concentration, the method of relaxation is needed by using Murottal Al-Qur'an. Purpose: To determine the effect of Murottal Al-Qur'an on level in concentration in fifth grade children with impaired concentration of learning in Sriamur Village. Methods: Design used pre-experimental through the One Group Pretest-Posttest approach with a purposive sampling technique and 19 samples of respondents. Using color and word test Stroops. Univariate data analysis using kolmogorov-smirnov and bivariate using Paired Sample T-Test. Results: There is the influence of Murottal Al-Qur'an on changes in concentration in fifth grade children with impaired concentration of learning in Sriamur Village with a value of p = 0,000 <α (0.05). Conclusion: There is The Influence Of Al-Qur'an Murottal On Concentration Level In Class V Children With Learning Concentration Disorders In Sriamur Village In 2020.